Features of tomato breeding in the Amur region. Results and perspectives - G. A. Kuzmitskaya; G. E. Shestopalova (Овощи России, 2021)
Relevance. Khabarovsk region is considered to be the zone of risky agriculture. It is characterized by the monsoon climate (july - september), having no analogies in Russia by univen distribution of precipitation, temperature drops and high natural infections background. That is why the search of tomato sorts, responsive to environmental changes, with increased or stable yield is highly relevant. The aim of our perennial researches in the creation of highly productive sorts and hybrids of tomato, most fully realizing natural and climatic conditions of cultivation, having higher stability to the most harmful diseases, stress environmental factors and high productive potential. The most significant limiting factors when growing tomatoes in the region are high natural infections background and sharply variable hydrothermal regime, formed under the influence of the Priamurye monsoon climate.Methods. The selection work had been made on vegetable plot of DV NIISH. The seedlings had been growing by cassette method into film greenhouse, which had been no had heating. Then the seedlings was planted out into open ground in accordance with bed technology recommended in the region by scheme 140 X 35 cm. The main method of selection work of new tomato sorts creation was analytical with continious selection. All the necessary phenological, biometrical and psychopathological observations and accounts had been done by generally accepted methodics.Results. The results in development of tomato selection in DV NIISH was the creation of sorts with different ripening time: early ripe – Zarya Vostokа and middle ripe – Amursky Utios and Dunyasha. They were included in the State registry of selection achievements in 2008 year. Sorts Klad and Galant passed successfully the state sort tests and were included in the state registry of selection achievements in 2017 and 2018 years. All these sorts are recommended for growing in garden plots, private plots and farms.